Reinventing Los Angeles nature and community in the global city - Gottlieb, Robert 1944- (MIT Press, 2007)
Describes how water politics, cars and freeways, and immigration and globalization have shaped Los Angeles, and how innovative social movements are working to make a more livable and sustainable city.